Resisting neoliberalism through political and social critique: The Guardian column of Polly Toynbee. (December 2015) - Bruce, Ian
Abstract: In this genre-based study I examined the discursive enactment of resistance to neoliberal ideology through the writing of Polly Toynbee in her regular commentary column in the Guardian newspaper. Using my social genre/cognitive genre model as the analytical framework (Bruce, 2008a ), I examined a sample of 30 examples of Toynbee׳s column in terms of the knowledge elements of context, epistemology, writer stance, content structuring and cognitive genres (text types). I found that, Toynbee׳s challenge to neoliberalism is two-pronged, involving the use of key generic elements to communicate themes that broadly fall within the areas of critique of the neoliberal shrinking of the state and advocacy of policy alternatives to strengthen social democracy and help the disadvantaged. Concerned with the embedded nature of neoliberalism in the British national psyche, which is reinforced by the powerful media organs, Toynbee, through her column presents a forceful, vigorous challenge to this prevailing ideology, a challenge achieved through a complex, discourse-constructing task. That complexity is revealed by the genre analysis undertaken here. Highlights: I investigated 30 example texts of a newspaper political commentary column. I explore how the writer, Toynbee, critiqued the ideology of neoliberalism. Her opposition encompassed two broad themes-the shrinking state and inequality. Advocacy of social justice was another important theme. A complex range of macro- and micro-level textual devices create the critique.